The Synergistic Effect of Tacrolimus (FK506) or Everolimus and Azoles Against Scedosporium and Lomentospora Species In Vivo and In Vitro - Zikuo Wang (Frontiers in Cellular and Infection Microbiology, 2022)
Scedosporium and Lomentospora infections in humans are generally chronic and stubborn. The use of azoles alone cannot usually inhibit the growth of these fungi. To further explore the combined effect of multiple drugs and potential mechanisms of action, we tested the antifungal effects of tacrolimus (FK506) and everolimus in combination with azoles in vitro and in vivo on 15 clinical strains of Scedosporium/Lomentospora species and detected the level of Rhodamine 6G, ROS activity, and apoptosis. The in vitro results showed that the combinations of tacrolimus with itraconazole, voriconazole, and posaconazole showed synergistic effects on 9 strains (60%), 10 strains (73%), and 7 strains (47%), respectively, and the combinations of everolimus with itraconazole, voriconazole, and posaconazole showed synergistic effects on 8 strains (53%), 8 strains (53%), and 7 strains (47%), respectively. The synergistic effects might correspond to the elevated ROS activity (the tacrolimus + itraconazole group compared to the itraconazole group, (P < 0.05)), early apoptosis (itraconazole (P < 0.05) and voriconazole (P < 0.05) combined with everolimus), and late apoptosis (the tacrolimus + itraconazole group compared to the itraconazole group, (P < 0.01); the tacrolimus + posaconazole group compared to the posaconazole group, (P < 0.05)), but not inhibition of efflux pump activity. Our in vitro results suggested that a combination of tacrolimus or everolimus and azoles have a synergistic effect against Scedosporium/Lomentospora. The synergistic mechanisms of action might be triggering excessive ROS activity and apoptosis. In vivo, the survival rate of G. mellonella (sixth instar larvae) was significantly improved by tacrolimus alone, everolimus alone, azoles alone, and tacrolimus and everolimus combined with azoles separately (P < 0.05 for the tacrolimus group; P < 0.01 for the everolimus group and the itraconazole group; P = 0.0001 for the tacrolimus and posaconazole group; P < 0.0001 for other groups except the everolimus and itraconazole group, everolimus and posaconazole group, and tacrolimus and itraconazole group). From the results, we infer that the combination of tacrolimus or everolimus with azoles has obvious synergistic effect on Scedosporium/Lomentospora, and might enhance the level of apoptosis and necrosis. However, the synergistic effects were not related to the efflux pump. In conclusion, from our in vitro and in vivo study, tacrolimus and everolimus combined with azoles may have a synergistic effect in the treatment against Scedosporium/Lomentospora, improving the drug activity of azoles and promoting a better prognosis for patients.